Genetic Diversity Analysis of Common Wild Rice By Using SSR Markers - Chao DONG; Feifei ZHANG; Cuifeng TANG; Xinxiang A; Shuxian GAN; Yayun YANG; Zidan LIU; Luyuan DAI (Guangdong nongye kexue)
【Objective】The study was conducted to reveal the genetic diversity of common wild rice (Oryza rufipogen Griff.) in Jinghong, Yuanjiang of Yunnan, Dongxiang of Jiangxi, and Myanmar, and the genetic variations of wild rice in Jinghong and Yuanjiang under in-situ and ex-situ conservation.【Methods】We detected the genetic diversities of 102 O. rufipogen samples from Yunnan Jinghong ex-situ and in-situ conservation zone, Yunnan Yuanjiang ex-situ and in-situ conservation zone, Jiangxi Dongxiang and Myanmar with 36 pairs of SSR markers. A comparison and cluster analysis of genetic diversities of O. rufipogen from different geographical sources and under different conservation methods was conducted.【Results】A total of 110 allele variations were detected, with an average of 3.056, and a range from 1 to 5. The average of Nei's gene diversity indexes (Ⅰ) was 0.448. The I of different geographical sources ranked as follows: Myanmar (0.561) > Yunnan Jinghong (0.437) > Yunnan Yuanjiang (0.236) > Jiangxi Dongxiang (0.230). The I of O. rufipogen under ex-situ conservation was higher than that under in-situ conservation in Jinghong (0.498 > 0.131) and Yuanjiang (0.264 > 0.035). Clustering and genetic differentiation analysis showed that the average genetic similarity coefficient (GS) of the tested materials was 0.772, with a range of 0.260-1.000. They were were divided into Yunnan Jinghong, Yunnan Yuanjiang, Jiangxi Dongxiang, and Myanmar populations at GS=0.635. The genetic distance of O. rufipogene between Yunnan Jinghong in-situ conservation and Myanmar was close (0.560), and that between Yunnan Yuanjiang in-situ conservation and Jiangxi Dongxiang was close (0.552). And the genetic difference of O. rufipogene between in-situ conservation of Yuanjiang and Jinghong was 0.748, indicating that there was obvious genetic differentiation between Yuanjiang and Jinghong.【Conclusion】The genetic differentiation of O. rufipogene has obvious regionalism. The genetic diversity of O. rufipogene decreased due to the decrease of in-situ conservation populations in Jinghong and Yuanjiang of Yunnan.